2005
DOI: 10.1016/s0011-393x(05)00062-7
|View full text |Cite
|
Sign up to set email alerts
|

Unit dosing of darbepoetin alfa for thetreatment of anemia in patients with end-stage renal disease being switched from recombinant human erythropoietin: Results of a phase IIIb, 27-week, multicenter, open-label study in Greek patients

Abstract: Background: Darbepoetin alfa is an erythropoiesis-stimulating glycoprotein with a -3-fold longer tl/2 and greater biological activity compared with recombinant human erythropoietin (rHuEPO).Objective: The objective of this study was to evaluate the efficacy and tolerability of long-term (24-week) darbepoetin alfa treatment in maintaining hemoglobin (Hb) concentrations in the target range of 10 to 13 g/dL in patients undergoing dialysis; the patients were switched from rHuEPO to a less-frequent dosing regimen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…By contrast, darbepoetin alpha (DA) that has an increased sialic acid carbohydrate content promotes decreased clearance and has a longer serum halflife than r-HuEPO [12][13][14], allowing a single weekly administration. Previous studies showed a similar potent effect of darbepoetin in adult as well as in paediatric patients either in pre-dialysis chronic renal failure or in end stage renal failure [8,[14][15][16][17][18][19]. The present study aims to determine the mean dose of darbepoetin necessary to achieve and maintain haemoglobin levels between 11.0 g/dl and 13.0 g/dl in CRF patients aged from 11 years to 18 years.…”
Section: Introductionmentioning
confidence: 86%
“…By contrast, darbepoetin alpha (DA) that has an increased sialic acid carbohydrate content promotes decreased clearance and has a longer serum halflife than r-HuEPO [12][13][14], allowing a single weekly administration. Previous studies showed a similar potent effect of darbepoetin in adult as well as in paediatric patients either in pre-dialysis chronic renal failure or in end stage renal failure [8,[14][15][16][17][18][19]. The present study aims to determine the mean dose of darbepoetin necessary to achieve and maintain haemoglobin levels between 11.0 g/dl and 13.0 g/dl in CRF patients aged from 11 years to 18 years.…”
Section: Introductionmentioning
confidence: 86%
“…Treatment-related adverse events were observed in 3% patients. 26 Many hemodialysis centers use darbepoetin-alfa as the preferred agent for the treatment of anemia in CKD patients. In a study 98 hemodialysis outpatients, were switched from twice to thrice weekly epoetin alfa to darbepoetin alfa.…”
Section: Efficacy In Patients On Dialysismentioning
confidence: 99%